Expertise and perceptual-cognitive performance in soccer: a review - Casanova, F.; Oliveira, J.; Williams, M.; Garganta, J. (Revista Portuguesa de Ciências do Desporto, 2009)
This review characterizes the importance of game intelligence between soccer players of different competition levels and according to a specific positional field status. However, research evidence on this topic is inconclusive and in some reports the importance of the perceptual-cognitive skills in the anticipation and decision-making performance remains unclear. Our intention is merely informative and indicative of the surrounding literature on the sport expertise, with the particular interest on the perceptual-cognitive performance, than depreciate some researches or taking part of some currents. Obviously that the variance in performance between soccer teams or players is depending of a several factors, like as anthropometric and physiological profiles, but one of the main factor that we want to include in the sport context is the perceptual-cognitive skills, such as visual search behaviour and the knowledge of situational probabilities. The aims of the present article are: (i) to define and to contextualize the different terminology used in this specific domain; (ii) to typify the different perceptual-cognitive skills that seems to bring on soccer players` performance; and (iii) to provide some future research guidelines.